Impacts of genetic bottlenecks on soybean genome diversity - Hyten, David L. (National Academy of Sciences, 2006)
Soybean has undergone several genetic bottlenecks. These include domestication in Asia to produce numerous Asian landraces, introduction of relatively few landraces to North America, and then selective breeding over the past 75 years. It is presumed that these three human-mediated events have reduced genetic diversity. We sequenced 111 fragments from 102 genes in four soybean populations representing the populations before and after genetic bottlenecks. We show that soybean has lost many rare sequence variants and has undergone numerous allele frequency changes throughout its history. Although soybean genetic diversity has been eroded by human selection after domestication, it is notable that modern cultivars have retained 72% of the sequence diversity present in the Asian landraces but lost 79% of rare alleles (frequency ≤0.10) found in the Asian landraces. Simulations indicated that the diversity lost through the genetic bottlenecks of introduction and plant breeding was mostly due to the small number of Asian introductions and not the artificial selection subsequently imposed by selective breeding. The bottleneck with the most impact was domestication; when the low sequence diversity present in the wild species was halved, 81% of the rare alleles were lost, and 60% of the genes exhibited evidence of significant allele frequency changes.